Towards an Inclusive Social Welfare Institution for Disabilities: The Case of Indonesia - Enung Huripah (Asian Social Work Journal, 2020)
People with disabilities are vulnerable to experience exclusion and discrimination in society. Likewise in Indonesia, a common condition for people with disabilities is the low level of participation in various sectors, such as the economy, education, healthcare, and public infrastructure. However, Indonesia has committed and started efforts to improve the equality of people with disabilities’ access. One institution that plays an important role in this regard is the social welfare institution. On a related note, this study discusses the dynamic of the social welfare institution’s roles in Indonesia in providing welfare for people with disabilities. Furthermore, the roles are explored based on the current context of society, which over the last few years, has been changing rapidly due to technological advancements, information acceleration, and big data utilization. This study argues building an inclusive social welfare institution is fundamental to fulfill the people with disabilities’ welfare. This study uses a qualitative approach with literature review and secondary data analysis as data collection methods.